2014
DOI: 10.1002/anie.201400723
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Interfacial Recombination in Aqueous Dye‐Sensitized Solar Cells by Octadecyltrichlorosilane Surface Treatment

Abstract: A general and convenient strategy is proposed for enhancing photovoltaic performance of aqueous dye-sensitized solar cells (DSCs) through the surface modification of titania using an organic alkyl silane. Introduction of octadecyltrichlorosilane on the surface of dyed titania photoanode as an organic barrier layer leads to the efficient suppression of electron recombination with oxidized cobalt species by restricting access of the cobalt redox couple to the titania surface. The champion ODTS-treated aqueous DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…It was successfully appliedt od yes 5 (MK2;S cheme 1), to give efficiencies of 2.99 and 4.10 %, respectively,t hrough coupling to TiO 2 films with transparent layerso fd ifferentt hicknesses (e.g.,2 .5 and 1.3 mm). [31] The cobalt-based DSSC wasa lso found to be more stable than the [Fe(CN) 6 ] 4À/3À -basedD SSC, as shown in Figure 10. Indeed, ar ecord efficiency was achieved for both zinc-porphyrin dyes [2] and metal-free dyes [4] through the use of ac obalt-basedr edox mediator.…”
Section: Monofunctional Electrolytesmentioning
confidence: 96%
See 1 more Smart Citation
“…It was successfully appliedt od yes 5 (MK2;S cheme 1), to give efficiencies of 2.99 and 4.10 %, respectively,t hrough coupling to TiO 2 films with transparent layerso fd ifferentt hicknesses (e.g.,2 .5 and 1.3 mm). [31] The cobalt-based DSSC wasa lso found to be more stable than the [Fe(CN) 6 ] 4À/3À -basedD SSC, as shown in Figure 10. Indeed, ar ecord efficiency was achieved for both zinc-porphyrin dyes [2] and metal-free dyes [4] through the use of ac obalt-basedr edox mediator.…”
Section: Monofunctional Electrolytesmentioning
confidence: 96%
“…[31] Restriction of oxidized redox mediators ([Co(bpy) 3 ] 3+ + )f rom getting access to the surface by such surface passivation effectively alleviates the dark currenta nd increasest he open-circuit voltage and, therefore, improves the cell conversion efficiency of aqueous DSSCs, as shown in Ta ble 2. By treatingt he MK2dyed TiO 2 with octadecyl trichlorosilane (ODTS), Spiccia et al were able to cover the undyed TiO 2 surfacew ith an alkyl siloxane network through SiÀOÀSi and SiÀOÀTi bond formation, as shown in Figure4.…”
Section: Anchorsmentioning
confidence: 99%
“…One of the main reasons is the recombination losses due to various defects at the interfaces in cells [12]. For DSSCs, there are two principal recombination places, one is the nanocrystalline TiO 2 particles/electrolyte or dye interface, the other is the transparent conductive substrate [typically fluorine doped tin oxide (FTO) glass]/electrolyte interface [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Efficiencies up to 13% have been obtained [18], and the scientific 42 research in this field is still very active towards new frontiers. Among these, the use of graphene as 43 counter electrode [19], the flexibilization of devices [20], the production of wire-shaped cells for 44 textile applications [21], the increase of performance and stability through multifunctional coatings 45 [22], the integration with water splitting devices [23], and the use of electrolytes with an aqueous 46 matrix [24,25] will be challenging and promising lands of success for the next decade. 47 One of the most active research areas in recent years is that of quasi-solid electrolytes, because 48 they demonstrated to be able to make DSSCs very stable over time, without significantly sacrificing 49 their efficiency with respect to the liquid counterparts [26,27].…”
Section: Introductionmentioning
confidence: 99%